Extensive mycetoma in forearm, chest and neck due to Nocardia mexicana - Arenas, Roberto; Damián-Magaña, Erika J; Sandoval-Navarro, Karla A; Torres-Bibiano, Balfré; Romero-Navarrete, Marina; Martínez-Chavarría, Luary C; Xicohtencatl-Cortes, Juan; Hernández-Castro, Rigoberto (The Journal of Infection in Developing Countries, 2024)
Introduction: Mycetoma is a chronic granulomatous inflammatory disease of the subcutaneous tissue, which affects deep structures and bone. Most cases of actinomycetoma are caused by members of the genus Nocardia. Case presentation: Here we report the case of a 43-year-old male who presented a disseminated mycetoma on the forearm, chest and neck, characterized by enlarged and erythematous lesions through which seropurulent material drains, and numerous atrophic scars. Molecular identification was performed by 16S gene amplification and sequencing. Nocardia mexicana was identified with 100% identity. Trimethoprim-sulfamethoxazole, diaminodiphenyl sulfone and amikacin was a successful treatment after 6 months. Conclusions: Nocardia mexicana is a rare organism that causes mycetoma. We report a case of extensive mycetoma on the forearm with spread to the neck and thorax associated with manipulation of the mouth of a calf.